1980
DOI: 10.1007/bf00587517
|View full text |Cite
|
Sign up to set email alerts
|

A new miniature plethysmograph to measure volume changes in small circumscribed tissue areas

Abstract: With an ultrasonic method tissue layer thickness was measured in man in circumscribed superficial tissue areas where the underlaying bone provided good backwall echos. In a 5 mm tissue layer changes of +/- 0.2% could be reliably detected. Knowing the height of the tissue cylinder between the surface of the skin and the bone allowed to calculate the tissue volume. The ultrasonic probes could therefore serve as miniature plethysmograph. Several probes were attached in the frontal region, sternum, along the verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…The weight of the probe and the Teflon ring together was 6.5 g. The coupling of the equipment with the tissues induced a deformation from an undisturbed level of less than 2%, assuming a subcutaneous tissue thickness between 2 and 8 mm. This was experimentally tested (Kirsch et al 1980;Gunga et al 1994bGunga et al , 1995. Based on the alterations in tissue thickness, the volume increase or decrease at the respective body areas could be determined.…”
Section: Fluid Distributionmentioning
confidence: 99%
“…The weight of the probe and the Teflon ring together was 6.5 g. The coupling of the equipment with the tissues induced a deformation from an undisturbed level of less than 2%, assuming a subcutaneous tissue thickness between 2 and 8 mm. This was experimentally tested (Kirsch et al 1980;Gunga et al 1994bGunga et al , 1995. Based on the alterations in tissue thickness, the volume increase or decrease at the respective body areas could be determined.…”
Section: Fluid Distributionmentioning
confidence: 99%
“…The fLEP was not affected by exercise in neither anatomical location, which may indicate that the measure is not as precise or sensitive as measurement of the thickness of cutis or subcutis. Changes in skin thickness have previously been detected with high frequency ultrasound minutes after intravenous fluid infusion (25) and after fluid redistribution due to gravitational stress (26, 27). The increase in thickness of cutis and subcutis on the distal thigh was probably induced by fluid effusion due to higher blood flow in the legs.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental conditions such as orthostasis, water immersion and heat exposure [12,17], effects of the microgravity environment on fluid shifts into and out of superficial tissues [18] could be accurately monitored noninvasively. These changes were established within a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Aukland [11] reported that, among other factors like water intake and renal excretion of salt and water, plasma volume (PV) is regulated by transferring surplus volume to the interstitium or by mobilizing fluid from this space by regulation of the net capillary filtration pressure. Volume changes in this interesting fluid compartment can be measured by ultrasound as recently published by Kirsch et al [12] and Gunga et al [13]. The aim of our study was to evaluate the changes in fluid compartment volume due to plasma refill by measuring the forehead tissue thickness (TT) using a novel hand-held ultrasound device.…”
Section: Introductionmentioning
confidence: 99%